Ultraviolet (UV‐C) radiation as a practical alternative to decontaminate thyme ( Thymus vulgaris L.) - Dogu‐Baykut, Esra; Gunes, Gurbuz (Wiley, 2018)
Alternative and cost‐effective decontamination methods for dehydrated herbs and spices are subject of interest in industry. In this work, a fluidized bed ultraviolet (UV‐C) system was tested for decontamination of dehydrated thyme. The samples were exposed to UV‐C radiation at 254 nm at 25.7, 51.4, 102.8, and 205.6 J/cm² delivered at an intensity of 26.7 mW/cm². UV‐C at 205.6 J/cm² resulted in 1.8, 1.3, and 0.3 log cfu/g reductions in total aerobic mesophilic bacteria, total yeast/mold, and Bacillus cereus, respectively. Total phenolic content, total antioxidant activity, moisture content, and the sensory attributes were not affected by the UV‐C treatments. UV‐C caused a small increase in L* and a* values but these changes were not detected in sensory evaluation. In conclusion, UV‐C treatment up to 205.6 J/cm² applied in a fluidized bed setting can potentially be used in decontamination of thyme without adverse effects on quality. PRACTICAL APPLICATIONS: UV‐C radiation is a widely used effective technology to reduce the microbial load on various surfaces, liquids, and air environments. In this study, the potential of a fluidized bed UV system was explored to reduce natural microbial load of thyme. The results indicated that UV‐C application may be an effective technology for decreasing the microbial load of thyme without inducing significant changes to the physical, chemical, and sensorial quality, therefore it has a potential as an alternative method for decontamination of thyme and similar herbs and spices industrially.